The Pediatric Tracheostomy Practice During COVID-19 Pandemic at a PICU - Neslihan Zengin; Alkan Bal; Osman Orkun Cankorur; Halil İbrahim Tanrıverdi (Galenos Yayinevi, 2022)
Introduction:To evaluate pediatric tracheostomies performed at a tertiary care pediatric intensive care unit (PICU) before and after the Coronavirus disease-2019 (COVID-19) pandemic.Methods:A total of 57 pediatric tracheostomy patients performed at a tertiary care PICU were included. Prognostic scores including pediatric risk of mortality 2, pediatric index of mortality 2 and pediatric logistic organ dysfunction scores, the family education process and time to home discharge were evaluated according to time of tracheostomy (pre-pandemic vs. after pandemic) and responsible surgeon (pediatric surgeon vs. otolaryngologist). MedCalc® Statistical Software version 19.7.2 (MedCalc Software Ltd, Ostend, Belgium; https: //www.medcalc.org; 2021) was used for statistical analysis.Results:A non-significant tendency for higher rate of pediatric surgery-based tracheostomies was noted after the pandemic (76.0 vs. 24.0%, p=0.134). No significant difference was noted between tracheostomies performed before vs. after the COVID-19 pandemic and those performed by otolaryngologists vs. pediatric surgeons in terms of prognostic scores and time to home discharge.Conclusion:Our findings emphasize the maintenance of high quality patient care for pediatric tracheostomy patients in accordance with standardized tracheostomy protocols and policies during the pandemic period with no significant difference between tracheostomies performed before and after the COVID-19 pandemic and those performed by pediatric surgeons vs. otolaryngologists in terms of prognostic scores and time to home discharge.